Gambaran Kesejahteraan Psikologis Pada Siswa Korban Bullying di SMA X Kota Banjarmasin - Oksarnalia, Prista; Marsha, Gladis Corinna; Fitriah, Aziza (Universitas Pahlawan Tuanku Tambusai, 2025)
Bullying in the school environment is still a serious problem that has a negative impact on students' well-being, both physically, psychologically and socially. This phenomenon creates an environment that does not support the optimal development of student potential, especially in the context of psychological well-being. This study aims to determine the description of psychological well-being students who are victims of bullying at SMA X Banjarmasin City. The method used a qualitative method with a phenomenological approach to two research subjects. Data collection used are semi-structured interviews and observation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The results of the study illustrate that the psychological well-being of students who are victims of bullying at SMA X Banjarmasin City is different based on the dimensions of psychological well-being. Students who are victims of bullying who have good psychological well-being are characterized by the fulfillment of four of the six dimensions, namely self-acceptance, environmental mastery, purpose in life, and personal growth. Meanwhile, students who are victims of bullying who have poor psychological well-being are characterized by the fulfillment of only two of the six dimensions, namely autonomy and purpose in life.